2020
DOI: 10.3390/pathogens9030172
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Root-Associated Bacterial Endophytes and Their Biocontrol Potential against Major Fungal Phytopathogens of Rice (Oryza sativa L.)

Abstract: Rice (Oryza sativa L.) is a major cereal food crop worldwide, and its growth and yield are affected by several fungal phytopathogens, including Magnaporthe oryzae, Fusarium graminearum, F. moniliforme, and Rhizoctonia solani. In the present study, we have isolated and characterized root-associated bacterial endophytes that have antifungal activities against rice fungal phytopathogens. A total of 122 root-associated bacterial endophytes, belonging to six genera (Bacillus, Fictibacillus, Lysinibacillus, Paenibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 70 publications
0
26
0
2
Order By: Relevance
“…Most of the bacteria isolated in our study from maize roots are known from the literature as rhizobacteria, many with a record as biocontrol agents on various crops including maize (e.g. Dardanelli et al 2012, Figueroa-López et al 2016, Shafi et al 2017, Khaskheli et al 2020. In addition to P. chlororaphis MA 342, Streptomyces antimycoticus FZB53-an agent with known anti-Fusarium activity (Koch and Löffler 2009)-and the model strain B. velezensis FZB42 (Fan et al 2018) were included as reference.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the bacteria isolated in our study from maize roots are known from the literature as rhizobacteria, many with a record as biocontrol agents on various crops including maize (e.g. Dardanelli et al 2012, Figueroa-López et al 2016, Shafi et al 2017, Khaskheli et al 2020. In addition to P. chlororaphis MA 342, Streptomyces antimycoticus FZB53-an agent with known anti-Fusarium activity (Koch and Löffler 2009)-and the model strain B. velezensis FZB42 (Fan et al 2018) were included as reference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that Pseudomonas are known to increase plant resistance to stress and pathogens [ 51 , 85 , 86 , 87 ]; however, to our knowledge, no studies on trees or with P. tremulae have been conducted thus far, though several older studies demonstrated the biocontrol capabilities of fungi against this pathogen [ 14 , 22 , 23 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, despite not being the focus of the present review, the potential of bacterial endophytes is noteworthy. Similar to what has been discussed, Khaskheli et al [ 141 ] addressed the importance of root-associated bacterial endophytes from rice plants to control its major diseases. They followed a similar approach and we recommend their work for additional material.…”
Section: Endophytes As Biocontrol Agentsmentioning
confidence: 93%